Improving the fatigue behaviour of a selectively laser melted aluminium alloy: Influence of heat treatment and surface quality. (15th August 2016) - Aboulkhair, Nesma T.; Maskery, Ian; Tuck, Chris; Ashcroft, Ian; Everitt, Nicola M.
Abstract: Selective laser melting (SLM) is being widely utilised to fabricate intricate structures used in various industries. Widening the range of applications that can benefit from such promising technology requires validating SLM parts in load bearing applications. Recent studies have mainly focussed on static loading, with minor attention to cyclic loading despite its vital importance in many applications. In this work, the fatigue performance of SLM AlSi10Mg was investigated considering the effects of surface quality and heat treatment. Compared to heat treatment, machining the samples played a minor role in improving the fatigue behaviour. This is potentially attractive to industries interested in latticed structures and topology-optimised parts where post-processing machining is not feasible. The characteristically fine microstructure in the as-built samples provided good fatigue crack propagation resistance but none of them survived nominal fatigue life of 3 × 10 7  cycles within the maximum stress range of 63–220 MPa. A specially-tailored heat treatment increased the material's ductility, significantly improving its fatigue performance. At 94 MPa, the heat-treated samples survived beyond the nominal fatigue life, outperforming the reference cast material. The combined effect of machining and heat treatment yielded parts with far superior fatigue properties, promoting the material for a wider range of applications. Graphical abstract: Highlights: The microstructure and fatigue performance of dense selectively laser melted AlSi10Mg were evaluated Machining did not improve the fatigue performance but rather worsened the reliability, opposing literature predictions A specially-tailored heat treatment significantly improved the fatigue performance without machining the surfaces Heat treating the samples with machined surfaced yielded the optimal fatigue performance, outperforming cast reference Improving the fatigue performance without post-process machining promotes fabricating hard to machine intricate structures